REST AREA DI KABUPATEN SINTANG - Glorian, Bima Septandry; Caesariadi, Tri Wibowo; Pebriano, Valentinus (JMARS: Jurnal Mosaik Arsitektur, 2025)
Sintang Regency is 386 kilometers from Pontianak City, the capital of West Kalimantan Province. According to the development plan for the eastern part of West Kalimantan Province. Sintang will be expanded to become the capital of Kapuas Raya Province. Although the plan has not been realized, Sintang Regency has grown rapidly. One of the areas that has grown rapidly is the Simpang Tebelian area located in Sungai Ukoi Village, Sungai Tebelian District because of its position at the intersection of the road to Melawi which is approximately 70 kilometers away. This location is imaginatively the gateway between Sintang and Melawi. So this location has the potential to be developed in the form of a transit area such as a rest area or other supporting areas for drivers to rest for a while before continuing their journey. Rest and service areas or generally better known as rest areas are places to rest for a while which are intended for drivers to be able to relax, relieve themselves, restore energy or even carry out religious obligations after traveling a long distance. The purpose of this design is to design a rest area in Sintang Regency as a place that accommodates transit activities or temporary stops in Sintang Regency. The design method consists of several stages, namely the preliminary stage, data collection stage, analysis stage, concept stage and design stage. The design results are in the form of a rest area in Sintang Regency as a transit activity container for drivers or road users with a building concept taking from the basic form of a traditional Dayak house which has an elongated shape and Malay which has three building periods and a terrace to show a local image.